Improvements and Maintenance of Clinical and Functional Measures Among Rural Women: Strong Hearts, Healthy Communities-2. 0 Cluster Randomized Trial. Issue 11 (15th November 2022) - Seguin-Fowler, Rebecca A.; Eldridge, Galen D.; Rethorst, Chad D.; Graham, Meredith L.; Demment, Margaret; Strogatz, David; Folta, Sara C.; Maddock, Jay E.; Nelson, Miriam E.; Ha, Seungyeon
Abstract : Background: Cardiovascular disease is the leading cause of death in the United States; however, women and rural residents face notable health disparities compared with male and urban counterparts. Community-engaged programs hold promise to help address disparities through health behavior change and maintenance, the latter of which is critical to achieving clinical improvements and public health impact. Methods: A cluster-randomized controlled trial of Strong Hearts, Healthy Communities-2.0 conducted in medically underserved rural communities examined health outcomes and maintenance among women aged ≥40 years, who had a body mass index >30 or body mass index 25 to 30 and also sedentary. The multilevel intervention provided 24 weeks of twice-weekly classes with strength training, aerobic exercise, and skill-based nutrition education (individual and social levels), and civic engagement components related to healthy food and physical activity environments (community, environment, and policy levels). The primary outcome was change in weight; additional clinical and functional fitness measures were secondary outcomes. Mixed linear models were used to compare between-group changes at intervention end (24 weeks); subgroup analyses among women aged ≥60 years were also conducted. Following a 24-week no-contact period, data were collected among intervention participants only to evaluate maintenance. Results: Five communities were randomized to the intervention and 6 to the control (87 and 95 women, respectively). Significant improvements were observed for intervention versus controls in body weight (mean difference: −3.15 kg [95% CI, −4.98 to −1.32]; P =0.008) and several secondary clinical (eg, waist circumference: −3.02 cm [−5.31 to −0.73], P =0.010; systolic blood pressure: −6.64 mmHg [−12.67 to −0.62], P =0.031; percent body fat: −2.32% [−3.40 to −1.24]; P <0.001) and functional fitness outcomes; results were similar for women aged ≥60 years. The within-group analysis strongly suggests maintenance or further improvement in outcomes at 48 weeks. Conclusions: This cardiovascular disease prevention intervention demonstrated significant, clinically meaningful improvements and maintenance among rural, at-risk older women. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03059472.